PROBLEMS OF TEACHING PHYSICS IN TECHNICAL UNIVERSITIES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article focuses on the importance and role of physics in teaching chemical technology and nanotechnology. Key concepts such as molecular physics, thermodynamics, and electrochemical processes are discussed, highlighting their significance in the development of new materials and technologies. The integration of theoretical knowledge with practical skills through laboratory work and the application of chemical reactions to optimize technological processes is emphasized. The article also highlights the importance of innovative technologies and new materials in contemporary sciences.